2005
DOI: 10.1002/pssb.200460002
|View full text |Cite
|
Sign up to set email alerts
|

Exciton delocalization of the J‐aggregate of oxacyanine dye and thiacyanine dye in LB films

Abstract: Delocalization and energy transfer of the molecular exciton of the J-aggregate of oxacyanine dye, N,N′-dioctadecyl-oxacyanine perchlorate (S9) in LB films have been examined. Fluorescence lifetime of the S9 J-aggregate (S9(J)) appears to be ca. 1/20 of the isolated S9 molecules (S9(M)), which suggests that the coherent size of the J-aggregate, N cohe , is about 22 at room temperature. Quenching of resonance fluorescence of S9(J) by thiacyanine dye, N,N′-dioctadecyl-thiacyanine perchlorate (S11) obeys the Stern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…In few cases two J-aggregate forming dyes with different J-band peak position have also been mixed to control the extent of aggregation [37][38][39]. Luminescence properties of the mixed Jaggregate consisting of two kinds of thiacarbocyanine dyes or naphthothiacarbocyanine dyes having meso-substituent have been studied by Y. Yonezawa et al [40] They also investigated the luminescence properties of the J aggregate of cyanine dyes in phospholipid langmuir-Blodgett films and exciton delocalization of the J-aggregate of oxacyanine dye and thiacyanine dye in LB films [41][42]. A.G. Vitukhnovsky et al Investigated the fluorescence properties of mixed J -aggregates of quinocyanine dyes [43].…”
Section: Dilution Experiments Of Nk J-aggregates In Otabmentioning
confidence: 99%
“…In few cases two J-aggregate forming dyes with different J-band peak position have also been mixed to control the extent of aggregation [37][38][39]. Luminescence properties of the mixed Jaggregate consisting of two kinds of thiacarbocyanine dyes or naphthothiacarbocyanine dyes having meso-substituent have been studied by Y. Yonezawa et al [40] They also investigated the luminescence properties of the J aggregate of cyanine dyes in phospholipid langmuir-Blodgett films and exciton delocalization of the J-aggregate of oxacyanine dye and thiacyanine dye in LB films [41][42]. A.G. Vitukhnovsky et al Investigated the fluorescence properties of mixed J -aggregates of quinocyanine dyes [43].…”
Section: Dilution Experiments Of Nk J-aggregates In Otabmentioning
confidence: 99%
“…One of the unique properties of J -aggregates is exciton migration over hundreds of monomers. , Due to this feature, J -aggregates can be considered as optical antenna for energy delivery purposes. ,, Exciton properties of J -aggregates are similar to those of light-harvesting complexes (LHC), which provide extremely fast and efficient energy transport of the absorbed sunlight to the photochemical reaction center of plants and photosynthetic bacteria. , Indeed, it was shown that the J -aggregates of cylindrical structure are the most promising artificial systems to mimic LHCs. , …”
Section: Introductionmentioning
confidence: 99%
“…(8). It can be seen that the decay of the fluorescence of the donor becomes faster when the concentration of acceptors increases due to the donor to acceptor energy transfer as it is experimentally observed [11]. It is shown that the fluorescence intensity increases from low concentration until a maximum is reached at c = 0.2.…”
Section: Mixed J-aggregates Of (S9/s11) Moleculesmentioning
confidence: 58%